2021
DOI: 10.1155/2021/4158495
|View full text |Cite
|
Sign up to set email alerts
|

OC‐STAMP Overexpression Drives Lung Alveolar Epithelial Cell Type II Senescence in Silicosis

Abstract: Cellular senescence has been considered an important driver of many chronic lung diseases. However, the specific mechanism of cellular senescence in silicosis is still unknown. In the present study, silicotic rats and osteoclast stimulatory transmembrane protein (Ocstamp) overexpression of MLE-12 cells were used to explore the mechanism of OC-STAMP in cellular senescence in alveolar epithelial cell type II (AEC2). We found an increasing level of OC-STAMP in AEC2 of silicotic rats. Overexpression of Ocstamp in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Research has shown that endoplasmic reticulum stress (ER stress) facilitates fibrotic remodeling through the activation of pro-apoptotic pathways, the induction of epithelial-mesenchymal transition, and the promotion of inflammatory responses [ 16 ]. Our previous studies discovered that both inflammation and ER stress play vital roles in the progression of silicosis [ 17 , 18 , 19 , 20 ]. It is worth noting that early studies on ER stress have focused on epithelial cells [ 16 , 18 , 19 ] with researchers since turning their attention to macrophages [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that endoplasmic reticulum stress (ER stress) facilitates fibrotic remodeling through the activation of pro-apoptotic pathways, the induction of epithelial-mesenchymal transition, and the promotion of inflammatory responses [ 16 ]. Our previous studies discovered that both inflammation and ER stress play vital roles in the progression of silicosis [ 17 , 18 , 19 , 20 ]. It is worth noting that early studies on ER stress have focused on epithelial cells [ 16 , 18 , 19 ] with researchers since turning their attention to macrophages [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies discovered that both inflammation and ER stress play vital roles in the progression of silicosis [ 17 , 18 , 19 , 20 ]. It is worth noting that early studies on ER stress have focused on epithelial cells [ 16 , 18 , 19 ] with researchers since turning their attention to macrophages [ 17 , 20 ]. Previous data indicated that silica inhalation might activate the Toll-like receptor 4 (TLR4)-nuclear factor kappa-B (NF-κB) signaling pathway in lung macrophages [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our preliminary study, we found that SiO 2 induced ER stress in A549 cells [ 7 ] and MLE-12 cells [ 8 ]. As a follow-up, this study was aimed at further investigating whether ER stress was also manifested in silica-induced macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) have been linked to lung fibrosis through the regulation of alveolar epithelial cell (AEC) apoptosis, epithelial–mesenchymal transition (EMT), fibroblast proliferation, myofibroblast differentiation, and M2 macrophage polarization [ 5 , 6 ]. Our previous studies also found that ER stress was abnormally activated in silica-induced A549 cells [ 7 ] and MLE-12 cells [ 8 ]. Other studies have shown that ER stress and the UPR were critical to the function and phenotypic transformation of macrophages [ 9 ].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation